1996
DOI: 10.1080/07391102.1996.10508896
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Mechanics and Dynamics Study of Alternate Triple-Helices Involving the Integrase-Binding Site of the HIV-1 Virus and Oligonucleotides Having a 3′-3′ Internucleotide Junction

Abstract: Triple helix formation by oligonucleotides can be extended beyond polypurine tracts with the help of specially designed linkers. In this paper we focus our attention on the integrase-binding site of the HIV-1 virus located on the U5 LTR end which contains two adjacent purine tracts on opposite strands. Two alternate triple helices with a 3'-3' junction in the third strand are considered: 5'-GGTTTTp3'-3'pTGTGT-5' and 5'-GGAAAAp3'-3'pAGAGA-5' The structural plausibility of these triplexes is investigated using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Short oligonucleotides also inhibit HIV IN, although their mode of inhibition is different. Firstly, it has been shown that a short single-stranded oligonucleotide targets a purine-rich motif in the viral longterminal-repeat ends, which leads to the formation of a DNA triple helix [149][150][151][152]. Secondly, oligonucleotides made up from deoxyguanosine and thymidine are potent IN inhibitors, with IC 50 values in the nanomolar range [70].…”
Section: Hiv In Inhibitorsmentioning
confidence: 99%
“…Short oligonucleotides also inhibit HIV IN, although their mode of inhibition is different. Firstly, it has been shown that a short single-stranded oligonucleotide targets a purine-rich motif in the viral longterminal-repeat ends, which leads to the formation of a DNA triple helix [149][150][151][152]. Secondly, oligonucleotides made up from deoxyguanosine and thymidine are potent IN inhibitors, with IC 50 values in the nanomolar range [70].…”
Section: Hiv In Inhibitorsmentioning
confidence: 99%
“…Two different mechanisms have been previously summoned to explain integrase inhibition by (G,A)‐ and (G,T)‐containing oligonucleotides: The first one involves formation of a short triple‐helix on the viral DNA extremity spanning over the integrase binding site. This hypothesis was first considered since a molecular modelling study suggested that the branched oligonucleotide OPC‐5′‐GGAAAA3′‐(CHOH) 3 ‐3′‐AGAGA‐5′‐OPC may form a thermodynamically stable triple helix on the U5 sequence [17]. To address that possibility, GA‐OPC 2 was assayed on the 3′‐processing of either a mutated LTR U5 extremity or the U3 DNA extremity (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Before these studies are discussed in more detail, molecular dynamics simulations on polyad‐containing structures are to be listed, however, for the reasons mentioned above. Simulations have been performed for triplexes135–142 and quadruplexes 31, 32, 143–147. In addition, more and more structural diverse RNA structures are studied.…”
Section: Computational Studies On Base Polyadsmentioning
confidence: 99%